Clozapine plasma level toxicity induced by a pharmacokinetic interaction with bupropion: A case report - Kelly N. Gable, PharmD, BCPP; Jaron Asher, MD (Mental Health Clinician)
Introduction Clozapine is the gold-standard antipsychotic treatment for patients with treatment-resistant schizophrenia. Prescribers must be vigilant in ensuring that all risk evaluation mitigation strategies requirements and routine cardiac and metabolic monitoring are maintained. Clozapine therapeutic drug monitoring is not a routine part of patient care; however, it can be clinically valuable to confirm the achievement of therapeutic dosages, address tolerability concerns, assess the impact of smoking habit changes, and identify concerning drug–drug interactions. Case Report A 52-year-old patient with a diagnosis of schizoaffective disorder was co-prescribed clozapine, bupropion, escitalopram, buspirone, and haloperidol since at least 2019. Clozapine/norclozapine levels were drawn in 2024 due to patient reports of daytime sedation. It was determined that the bupropion should be discontinued, and it was reduced from 300 mg to 150 mg daily for 1 week and then completely stopped. A final documented clozapine/norclozapine plasma level was obtained 4 weeks later, demonstrating a significant decrease in levels. The experience of daytime sedation was reported to be mildly improved by the patient. Discussion There are multiple published reports of established pharmacokinetic and pharmacodynamic drug–drug interactions with clozapine. In this case report, there was a direct correlation between clozapine (CYP2D6 substrate) plasma levels decreasing and the discontinuation of bupropion (CYP2D6 inhibitor). Conclusion This case demonstrates a low-patient harm example of how a pharmacokinetic drug interaction with clozapine can unexpectedly impact patient care. Clozapine plasma level or concentration monitoring can serve as one of the tools necessary to guide the identification of drug–drug interactions.